Nonmetallic Mineral as the Carrier of TiO2 Photocatalyst: A Review - Xie, Yan; Wang, Jiao; Ren, Fengguo; Shuai, Huan; Du, Gaoxiang (Frontiers in Catalysis, 2022)
The composite photocatalyst can be constructed by using natural porous minerals with a wide range of sources, low prices and stable chemical properties as the titanium dioxide catalyst carrier, which can not only reduce the cost of catalyst preparation and application, but also effectively improve the dispersion, recyclability and catalytic performance of the catalyst. In recent years, a large number of scientific researchers have conducted a lot of research on the preparation and performance of porous mineral-supported composite catalytic materials. This paper describes the catalytic mechanism of titanium dioxide, as well as the research and application progress of various nonmetallic mineral materials supported by titanium dioxide, and prospects the development trend in the future.